Blood-brain barrier breakdown in the aging human hippocampus - Montagne, Axel; Barnes, Samuel R; Sweeney, Melanie D; Halliday, Matthew R; Sagare, Abhay P; Zhao, Zhen; Toga, Arthur W; Jacobs, Russell E; Liu, Collin Y; Amezcua, Lilyana; Harrington, Michael G; Chui, Helena C; et al. (Neuron (Cambridge, Mass.), 2015)
The blood-brain barrier (BBB) limits entry of blood-derived products, pathogens, and cells into the brain that is essential for normal neuronal functioning and information processing. Post-mortem tissue analysis indicates BBB damage in Alzheimer's disease (AD). The timing of BBB breakdown remains, however, elusive. Using an advanced dynamic contrast-enhanced MRI protocol with high spatial and temporal resolutions to quantify regional BBB permeability in the living human brain, we show an age-dependent BBB breakdown in the hippocampus, a region critical for learning and memory that is affected early in AD. The BBB breakdown in the hippocampus and its CA1 and dentate gyrus subdivisions worsened with mild cognitive impairment that correlated with injury to BBB-associated pericytes, as shown by the cerebrospinal fluid analysis. Our data suggest that BBB breakdown is an early event in the aging human brain that begins in the hippocampus and may contribute to cognitive impairment.